Strategies and Obstacles in Bahasa Indonesia Acquisition Experienced by Six Foreign Teachers in Indonesia - Anita Widiprastyanti; Elmi Erinta; Meykke Alvia Yuntiawati; Listyani Listyani; Krismiyati Krismiyati (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2025)
This study explores the strategies and challenges faced by six foreign teachers in learning the Indonesian language at an international school in Semarang, Central Java. Foreign teachers are increasingly playing significant roles in education in Indonesia, yet they often encounter difficulties in adapting to local linguistic and cultural norms. Using a qualitative case study approach, data were collected through semi-structured interviews and field notes. The findings reveal that the main challenges experienced by foreign teachers include differences between formal and informal language use, pronunciation difficulties, grammatical complexity, dialect variations, limited opportunities for practice, and a tendency toward code-switching. To overcome these challenges, the teachers employed strategies such as community support, immersive learning through real-life practice, attending formal classes, self-study, and using language applications. Among these strategies, community support and immersive learning proved to be the most effective in enhancing fluency and cultural understanding, while formal classes provided a strong foundation in grammar and vocabulary. This study highlights the importance of combining immersive experiences with structured learning to support successful language acquisition for foreign teachers in Indonesia. The findings are expected to provide practical contributions for educational institutions in designing language support programs and promoting more inclusive cultural integration.Â